Polypharmacy in patients with multiple sclerosis and the impact on levels of care and therapy units - Brüggemann, Finn; Gross, Stefan; Süße, Marie; Hok, Pavel; Strauss, Sebastian; Ziemssen, Tjalf; Frahm, Niklas; Zettl, Uwe K.; Grothe, Matthias (Frontiers in Neurology, 2023)
Background The aim of this study was to examine the societal costs of polypharmacy in patients with multiple sclerosis (MS). We therefore focused on the association between the number of medications on the level of care (LOC), the German classification of the need for care, and the number of therapy sessions (TTU). Methods In addition to demographic information and medication, 101 MS patients performed the Multiple Sclerosis Health Resource Utilization Survey (MS-HRS). Medications were subdivided into a total number of medications (TD), MS-related medication [MSD, i.e., disease-modifying drugs (DMDs) and symptomatic treatment (SD)], and medication for comorbidities (CDs). Multivariate linear regression models were performed to estimate if the amount of each medication type affects LOC or TTU. Results Polypharmacy appeared in 54 patients at the time of the survey. The relative risk (RR) of LOC 1 increased significantly by 2.46 (p = 0.001) per TD and by 2.55 (p = 0.004) per MSD, but not per CD (RR 1.44; p = 0.092). The effect of RR on MSD was driven by SD (RR 2.2; p = 0.013) but not DMD (RR 2.6; p = 0.4). RR of MSD remained significant for LOC 2 (1.77; p = 0.009) and LOC 3/4 (1.91; p = 0.015), with a strong trend in RR of SD, but not DMD. TTU increased significantly per MSD (p = 0.012), but not per TD (p = 0.081) and CD (p = 0.724). Conclusion The number of MSDs is related to the likelihood of a higher level of care and the number of therapy sessions and is therefore a good indication of the extent of the societal costs.